Expert consensus on the diagnosis and treatment of NTRK gene fusion solid tumors in China. Issue 21 (20th September 2022) - Xu, Chunwei; Si, Lu; Wang, Wenxian; Li, Ziming; Song, Zhengbo; Wang, Qian; Liu, Aijun; Yu, Jinpu; Fang, Wenfeng; Zhong, Wenzhao; Wang, Zhijie; Zhang, Yongchang; et al.
Abstract: Gene fusions can drive tumor development for multiple types of cancer. Currently, many drugs targeting gene fusions are being approved for clinical application. At present, tyrosine receptor kinase (TRK) inhibitors targeting neurotrophic tyrosine receptor kinase ( NTRK ) gene fusions are among the first "tumor agnostic" drugs approved for pan‐cancer use. Representative TRK inhibitors, including larotrectinib and entrectinib, have shown high efficacy for many types of cancer. At the same time, several second‐generation drugs designed to overcome first‐generation drug resistance are undergoing clinical development. Due to the rarity of NTRK gene fusions in common cancer types and technical issues regarding the complexity of fusion patterns, effectively screening patients for TRK inhibitor treatment in routine clinical practice is challenging. Different detection methods including immunohistochemistry, fluorescence in situ hybridization, reverse transcription‐polymerase chain reaction, and (DNA and/or RNA‐based) next‐generation sequencing have pros and cons. As such, recommending suitable tests for individual patients and ensuring the quality of tests is essential. Moreover, at present, there is a lack of systematic review for the clinical efficacy and development status of first‐ and second‐generation TRK inhibitors. To resolve the above issues, our expert group has reached a consensus regarding the diagnosis and treatment of NTRK gene fusion solid tumors, aiming to standardize clinical practice with the goal of benefiting patients with NTRK gene fusions treated with TRK inhibitors. Abstract : To improve the diagnosis and treatment of NTRK gene fusion solid tumors in China, we reached consensus on detection strategy based on cancer type classification, quality control requirements, treatment and clinical management. Moreover, we systematically reviewed the clinical efficacy, resistance mechanisms and development status of TRK inhibitors.